The role of the Herzliya Institute in Israeli decision-making - Shamali, Elham Jabr Salm; Kishko, Nedaa Mohamad (Journal of Humanities & Social Sciences, 2023)
The Herzliya Center played an important role in Israeli decision-making on several levels. This center was established by the former National Security Adviser, General Uzi Arad, after the failure of the Camp David peace conference with the Palestinians in 2000 AD. Based on the nature of the study, the historical approach was used in this research study, where Focus was placed on the nature of the center, and its most important decisions and recommendations in its sessions held in Israeli decision-making, as the study showed that the center has a major role in Israeli decision-making and foreign relations in all its forms. The study recommended the need to expand and pay attention to studying the role of Israeli research centers in decision-making, and to attract more researchers and specialists in Israeli affairs to support security and national issues, and to provide more studies and research in the field of decision-making, and the content of their relations with Palestinian, Arab, and Islamic affairs. * This research was conducted under the supervision of Al-Messiri Academy for Research and Studies, and the funding of the Strategic Initiative Center, Palestine-Malaysia.